The faith of biology and the biology of faith : order, meaning, and free will in modern medical science. - Pollack, Robert, 1940- (Columbia series on religion and politics., 2013)
Are there parallels between the ""moment of insight"" in science and the emergence of the ""unknowable"" in religious faith? Where does scientific insight come from? Award-winning biologist Robert Pollack argues that an alliance between religious faith and science is not necessarily an argument in favor of irrationality: the two can inform each other's visions of the world. Pollack begins by reflecting on the large questions of meaning and purpose?and the difficulty of finding either in the orderly world described by the data of science. He considers the obligation to find meaning.